Kazakhstan Engineering: new vectors of development. - Chermoshentseva, Y. V. (Journal of Economic Research & Business Administration, 2015)
Mechanical engineering is the most important sector of the economy of any industrialized th state. Produced all sorts of equipment, machinery, tools, appliances, and consumer goods, machi-nery ensures the stability of agro-industrial activities of the complex, energy and metallurgical sec-tors, transportation and other key industries. Sustainable development and reliable functioning of engineering largely determine the energy and material economy, productivity, level of environmental safety of industrial production and, ultimately, the economic security of the country. Today in Kazakhstan engineering there are systemic problems insufficient level of investment attractiveness of the industry, low competitiveness of products in the domestic and foreign markets, the lack of qualified personnel. This article examines the current state of the machine-building complex of the Republic of Kazakhstan, identifies the most pressing problems and suggested priorities for the de-velopment of the industry.